Peran Lembaga Advokasi Anak Dalam Mendampingi Anak Yang Melakukan Tindak Pidana (Studi Kasus Di Yayasan Atma Surakarta). - Safitri, Dwi, Kuswardani, SH.M.Hum (2017)
Children naughtiness which is often to be called as relevant behavior indirectly its turn out the children to make them do criminal and another penal law acts in their young of age. As the children who did offence the law or criminal act (trouble with law), often their rights unprotected. The conditions and matters of the children (minor), sometimes in such a way have been ignored without any special treatment. It should be the children have legal aid such like adults when they face law problem, but in the fact children directly face it without any proper legal aid, plus society stigma which is sometimes criticized them very spicy and often excommunicated them because they has become criminal. This condition obviously affects their psychiatric (mental). The presence of the advocacy institution specifically ATMA foundation is embodiment of concerns from a group of which is care and have attention in children issues, care and committed to fight children rights fulfillment especially children as criminals.